When Do Teachers Respond to Student Feedback? Evidence from a Field Experiment - Margaretha Buurman; Josse Delfgaauw; Robert Dur; Robin Zoutenbier (Institute of Labor Economics (IZA), 2020)
We ran a field experiment at a large Dutch school for intermediate vocational education to examine whether the response of teachers to student feedback depends on the content of the feedback. Students evaluated all teachers, but only a randomly selected group of teachers received feedback. Additionally, we asked all teachers before as well as a year after the experiment to assess their own performance on the same items. We find a precisely estimated zero average treatment effect of receiving student feedback on student evaluation scores a year later. However, teachers whose self-assessment before the experiment is much more positive than their students' evaluations do improve significantly in response to receiving feedback. We also find that provision of feedback reduces the gap between teachers' self-assessment and students' assessment, but only to a limited extent. All of these results are driven by the female teachers in our sample; male teachers appear to be unresponsive to student feedback.
Keywords: C93; I2; M5; 330; field experiment; feedback; teachers; student evaluations; self-assessment; gender differences